Pengaruh Komunikasi dan Strea Kerja terhadap Kepuasan Kerja Karyawan pada PT PLN (Persero) Unit Pelayanan Pelanggan Medan Selatan - Al-Imanda, Maulana Amin; Supriadi, Supriadi; Fauzi, Fauzi (JRMB (Jurnal Riset Manajemen & Bisnis), 2022)
The formulation of the problem in this study is whether communication affects job satisfaction, whether job stress affects job satisfaction and whether communication and job stress affect employee job satisfaction at PT PLN (Persero) South Medan Customer Service Unit. The purpose of this study was to determine the effect of communication and job stress on employee job satisfaction both partially and simultaneously. The sample used in this study were all employees of the South Medan Customer Service Unit of PT PLN (Persero), totaling 45 employees. The data collection technique used is by distributing questionnaires / questionnaires to respondents, interviews with related parties, documentation studies and literature studies. The stages of data analysis are conducting validity and reliability tests, classical assumption tests with normality, heteroscedasticity and multicolonierity tests, to determine the direction of the relationship between the independent variable and the dependent variable, multiple linear regression analysis is carried out and hypothesis testing is carried out t test, F test and determination test. The results of the analysis and hypothesis testing show that communication has a positive and significant effect on employee job satisfaction, job stress has a positive and significant effect on employee job satisfaction and communication and job stress have a significant effect on employee job satisfaction at PT PLN (Persero) South Medan Customer Service Unit